2016
DOI: 10.1186/s12893-016-0142-5
|View full text |Cite
|
Sign up to set email alerts
|

A survey on beliefs and attitudes of trainee surgeons towards placebo

Abstract: BackgroundThe aim of this study was to investigate the beliefs and attitudes of trainee surgeons regarding placebo interventions, in surgical practice and in research, and to compare them to those of senior orthopaedic surgeons.MethodsAn invitation to participate in an online survey was sent to all the email addresses in the members’ database of the British Orthopaedic Trainees Association (BOTA).ResultsAll 987 members of BOTA were invited to participate in the survey and 189 responded (19 %). The majority of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 24 publications
4
32
0
1
Order By: Relevance
“…Although previous studies have not been conducted in the field of orthopaedic physical therapy, some considerations can be made when comparing our results with a similar survey performed among other healthcare professions[1939]. Similarly to previous surveys among physicians[25,28,29,32], almost 70.0% of OMTs defined CFs as an intervention without a specific effect, but with a possible non-specific effect. These findings reveal that physical therapists conceptualize the context around the treatment as an incidental element that can occur during treatment[61] instead of a powerful therapeutic tool capable of influencing patients’ outcome[56].…”
Section: Discussionsupporting
confidence: 56%
“…Although previous studies have not been conducted in the field of orthopaedic physical therapy, some considerations can be made when comparing our results with a similar survey performed among other healthcare professions[1939]. Similarly to previous surveys among physicians[25,28,29,32], almost 70.0% of OMTs defined CFs as an intervention without a specific effect, but with a possible non-specific effect. These findings reveal that physical therapists conceptualize the context around the treatment as an incidental element that can occur during treatment[61] instead of a powerful therapeutic tool capable of influencing patients’ outcome[56].…”
Section: Discussionsupporting
confidence: 56%
“…The adoption of placebo strategies seems to be common practice in clinical routine among healthcare providers [ 193 ]. In musculoskeletal field, orthopedics surgeon, rheumatology physicians and nurses thought that placebo effects are real, have therapeutic benefits, and are permissible within the ethical borders [ 194 196 ]. Patients with chronic musculoskeletal pain and rheumatologic complaints know what placebo effects are, consider placebo treatments acceptable when adopted as complementary/adjunct treatments and when no other established treatments are available.…”
Section: Clinical Applications and Translational Researchmentioning
confidence: 99%
“…Survey responses from 189 members of the British Orthopaedic Trainees Association revealed that of those who preferred a sham-control design over an active-control, 30% stated they would 'definitely' recruit patients for a sham surgery trial, and 56% stated they would 'probably'. 41 Surgeon willingness to participate in a clinical trial may also depend, at least in part, on remuneration. A pragmatic obstacle for sham surgical trials in orthopaedics is whether payers will reimburse for it.…”
Section: Discussionmentioning
confidence: 99%